Estudio de la variabilidad genética en habichuela Phaseolus vulgaris L., mediante descriptores morfológicos y bioquímicos - Tofiño Rivera, Adriana Patricia; Gutiérrez, J.A.; Ocampo Nahar, César H.; García, V.H. (2004)
Genetic variability of 116 accesions of Phaseolus vulgaris showing snap beans characteristics coming from primary and secondary centers of domestication, were studied using eighteen morphological descriptors to characterize pods and seeds, SDS-PAGE analysis of seed phaseolins and eight isozyme systems. Higher morphological diversity and best pod marketing characteristics were found at Andean accessions. After SDS-PAGE analysis Andean (T, C, and H) and Mesoamerican [S, Sb, CH and H(S+1)] types of phaseolin were detected in the sample, suggesting a higher contribution of the Mesoamerican gene pool to the genotype of snap beans. Also it was observed that, at the same zones of collection in some secondary centers, snap beans were originated and dispersed differently as compared to dry beans. A higher number of hybrid genotypes were detected among genetic pools when the three markers were used. Results seems to indicate that snap beans developed under environmental effects of the temperate zones, have a more complex genetic structure and higher rates of allogamy than those observed at primary centers of domestication. The results obtained using the three descriptors show that total genetic diversity for snap beans is similar to that of dry beans, but the snap beans population structure observed in this study is different to that reported for dry beans. Key words: Genetic variability, morphological descriptors, isozymes, seed protein, genetic pool.